2021
DOI: 10.3390/diagnostics11071253
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Diagnosis: Simplified Solutions, Predictive Barriers, and Future Promises

Abstract: The simplification of current hepatitis C diagnostic algorithms and the emergence of digital diagnostic devices will be very crucial to achieving the WHO’s set goals of hepatitis C diagnosis (i.e., 90%) by 2030. From the last decade, hepatitis C diagnosis has been revolutionized by the advent and approval of state-of-the-art HCV diagnostic platforms which have been efficiently implemented in high-risk HCV populations in developed nations as well as in some low-to-middle income countries (LMICs) to identify mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 109 publications
0
23
0
Order By: Relevance
“…More innovative HCV screening strategies could still improve both time to HCV RNA testing and treatment uptake. Multiple clinic visits for assessment and testing, and the delay in availability of test results are considered as major barriers in the HCV care continuum, resulting in attrition at each subsequent visit [ 21 ]. Studies from the high-income countries have reported that 46% to 73% of people with HCV antibodies receive RNA testing, [ 22 , 23 ] and within low and middle-income countries, this proportion may be lower.…”
Section: Discussionmentioning
confidence: 99%
“…More innovative HCV screening strategies could still improve both time to HCV RNA testing and treatment uptake. Multiple clinic visits for assessment and testing, and the delay in availability of test results are considered as major barriers in the HCV care continuum, resulting in attrition at each subsequent visit [ 21 ]. Studies from the high-income countries have reported that 46% to 73% of people with HCV antibodies receive RNA testing, [ 22 , 23 ] and within low and middle-income countries, this proportion may be lower.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who achieve an SVR have less mortality than do those without SVR after treatment. Treatment has better effects on disease outcomes if it is started before cirrhosis[ 109 ]. To prevent long-term liver disease and HCV spread, antiviral therapy should be available in childhood.…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…Due to negative previous experiences of primary healthcare and specialized hospital care services, some patients were reluctant to initiate testing. POC and DBS have proven effective in HCV testing, diagnostics, and treatment [ 24 ]. In our real-life setting, we found that special expertise and methods were often needed due to difficulties in taking HCV RNA samples from intravenous drug users who had collapsed veins.…”
Section: Discussionmentioning
confidence: 99%
“…Besides using standard venous blood tests, HCV can be detected using point-of-care (POC) diagnostic methods. Of the POC methods, a dry blood spot (DBS) test is especially valuable for patients, as it provides an opportunity for HCV screening, diagnosis, and treatment with a low financial threshold without a need to purchase expensive equipment [ 23 , 24 ]. The use of POC methods aimed to increase the proportion of patients taking laboratory tests at their own initiative by removing the requirement to refer the patient to an external laboratory, and in addition to alleviating sample extraction from patients with a history of injecting drugs and collapsed veins.…”
Section: Methodsmentioning
confidence: 99%